Extrapulmonary pleuropulmonary blastoma in a 3-year-old child: A case report and review of literature - Mokarram Ali; Muneer Abas Malik; Nitin James Peters; Manasa Reddy; Ram Samujh (Journal of Indian Association of Pediatric Surgeons, 2021)
Pleuropulmonary blastomas (PPBs) are very rare, highly aggressive, dysembryonic neoplasms of thoracopulmonary mesenchyme. These have been reported in the pediatric population and account for only 0.5%–1% of all primary malignant lung cancers. They normally arise from lung tissue, however rarely the parietal pleura may be the tissue of origin (extra pulmonary PPB) which are extremely rare. Common age of presentation is three to 4 years. The prognosis is poor with distant metastasis to central nervous system and bone with survival rate of approximately 42.9% at 5 years. They are managed by aggressive multimodal therapies including surgery and chemotherapy. We report a case of a 3-year-old male child with Type 2 PPB of the left hemithorax, managed by surgical excision of the mass and adjuvant chemotherapy.